Gulella Bicolor (Hutton) in Texas - Thomas G. Littleton (Hello World!, 1975)
Gulella bicolor was collected alive by the author under the leaf litter of a shrub near the U.S.D.A. Research Laboratory in Weslaco, Hidalgo County, Texas in 1971 and 1973. As several specimens were collected each time it would appear that G. bicolor may be establishing itself in the general vicinity of the laboratory.